Impact of Age on Predictive Capabilities of Ferritin, Ferritin-Hemoglobin Ratio, IL-6, and sIL-2R for COVID-19 Severity and Mortality - Skakun, Oleksii; Vandzhura, Yaroslava; Vandzhura, Ihor; Symchych, Khrystyna; Symchych, Anton (Acta medica (Hradec Kralove), 2024)
The study aimed to establish the impact of age on the predictive capability of ferritin, ferritin-hemoglobin ratio (FHR), IL-6, and sIL-2R in COVID-19 patients. Compared to patients with moderate condition, patients with severe condition had higher ferritin level (441.0 [188.0-829.8] ng/mL vs 281.0 [172.0-388.0] ng/mL, p = 0.002), sIL-2R level (6.0 [4.7-9.0] pg/mL vs 5.3 [3.7-6.9] pg/mL, p = 0.020), FHR (38.4 [15.1-63.4] vs 22.0 [12.1-32.1], p = 0.002). The area under the curves (AUC) for discriminative capabilities of the following biomarkers for severe condition were assessed in patients aged <65 years and patients aged ≥65 years: ferritin (AUC = 0.585, p = 0.309 vs AUC = 0.683, p = 0.002), FHR (AUC = 0.589, p = 0.302 vs AUC = 0.688, p = 0.002), IL-6 (AUC = 0.503, p = 0.972 vs AUC = 0.647, p = 0.019), and sIL-2R (AUC = 0.549, p = 0.552 vs AUC = 0.646, p = 0.017). Also AUCs for discriminative capabilities for in-hospital mortality were compared in patients aged <65 years and ≥65 years: ferritin (AUC = 0.607, p = 0.628 vs AUC = 0.661, p = 0.105), FHR (AUC = 0.612, p = 0.621 vs AUC = 0.688, p = 0.002), IL-6 (AUC = 0.580, p = 0.724 vs AUC = 0.695, p = 0.016), and sIL-2R (AUC = 0.620, p = 0.491 vs AUC = 0.695, p = 0.029). Thus, ferritin, FHR, IL-6, and sIL-2R didn't show acceptable predictive value for severe condition and lethal outcome in patients aged <65 years but had high predictive value for lethal outcome in patients aged ≥65 years.
Keywords: biologické markery; Aged; Hemoglobins; Aged, 80 and over; stupeň závažnosti nemoci; Interleukin-6; Age Factors; lidé středního věku; senioři; Severity of Illness Index; Receptors, Interleukin-2; receptory interleukinu-2; lidé; Middle Aged; hemoglobiny; ferritin; Predictive Value of Tests; Female; senioři nad 80 let; Biomarkers; věkové faktory; COVID-19; Male; ženské pohlaví; Humans; mužské pohlaví; SARS-CoV-2; interleukin-6; prediktivní hodnota testů; Ferritins